Antibacterial Activity Test of Various Ethanol Solvent Concentrations Extract of Sweet Orange (Citrus sinensis) Peel on Escherichia coli, Shigella dysenteriae, and Salmonella typhii - Purba, Tabitha S. G.; Tobing, Joshua H. L. (Jurnal Biologi Tropis, 2025)
The rise of antibiotic resistance necessitates the discovery of new antibacterial agents. Sweet orange (Citrus sinensis) peel often considered waste, contains bioactive compounds with potential antimicrobial properties. This study aimed to evaluate the antibacterial activity of ethanol extracts from sweet orange peel on Escherichia coli, Shigella dysenteriae, and Salmonella typhii. This laboratory experimental study uses sweet orange peel extracted by maceration using 30%, 40%, and 50% ethanol as solvent. The highest average inhibition zones were observed at the 50% concentration for all bacteria: E. coli (7,683 mm), S. typhii (8,400 mm), and S. dysenteriae (7,250 mm). Statistical analysis confirmed that the extract concentration has a very significant effect (p = 0,000) on the inhibition zone, with higher concentrations yielding larger zones. A significant interaction was also found between the type of bacteria and time (p = 0,000). Ethanol extract of sweet orange (Citrus sinensis) peel has moderate antibacterial activity against Escherichia coli, Shigella dysenteriae, and Salmonella typhii. Its effectiveness is concentration-dependent, with the 50% ethanol extract shows the strongest inhibition. This suggests that orange peel waste is a promising source of natural antibacterial compounds.